SYNERGY BETWEEN THE PENTA-HELIX MODEL AND COMMUNITY DEVELOPMENT IN ACCELERATING SUSTAINABLE TOURISM VILLAGES: A CASE STUDY OF KASSI TOURISM VILLAGE, JENEPONTO REGENCY - Andi Asyifah Rizky Nasta; Nur Asyifa T; Muhammad Iqbal (Universitas Cahaya Prima, 2026)
Developing a sustainable tourism village requires collaboration among multiple stakeholders and active community participation. The Pentahelix model provides a collaborative framework involving government, business, academia, communities, and media, while community development strengthens local capacity, participation, institutions, and economic opportunities. This study analyzes the synergy between the Pentahelix model and community development in accelerating the development of Kassi Tourism Village, Rumbia District, Jeneponto Regency. A qualitative Systematic Literature Review (SLR) was employed using scholarly articles, policy documents, and relevant literature on collaborative governance, the Pentahelix model, and community development. The findings reveal that Kassi Tourism Village possesses significant natural, cultural, and man-made tourism attractions, supported by community-based tourism services such as homestays, local culinary products, and tour guiding. Although all Pentahelix actors are involved, collaboration remains fragmented due to inconsistent stakeholder commitment, limited institutional coordination, inadequate infrastructure, weak promotion, and insufficient human resource capacity. Community development has strengthened local participation through the involvement of the village government, Tourism Awareness Group (Pokdarwis), Youth Organization (Karang Taruna), Village Consultative Body (BPD), and local entrepreneurs. The study concludes that sustainable tourism development requires institutionalized Pentahelix collaboration supported by continuous capacity building, participatory decision-making, effective communication, and equitable distribution of tourism benefits to enhance local resilience and long-term sustainability